Enhancing Micropipette Aspiration with Artificial-Intelligence Analysis - Abarca-Ortega, A (Elsevier B.V., 2024)
The micropipette-aspiration technique is commonly used in the field of mechanobiology, offering a variety of measurement types. To extract biophysical parameters from the experiments, numerical analysis is required. Although previous works have developed techniques for the partial automation of these analyses, these approaches are relatively time consuming for the researchers. In this article, we describe the development and application of an artificial-intelligence tool for the completely automatic analysis of micropipette-aspiration experiments. The use of this tool is compared with previous methods and the impressive reduction in the time required for these analyses is discussed. The new tool opens new possibilities for the micropipette-aspiration technique by enabling dealing with large numbers of experiments and real-time measurements. © 2024 Biophysical Society